2014
DOI: 10.1042/cs20140215
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-(1–7) decreases skeletal muscle atrophy induced by angiotensin II through a Mas receptor-dependent mechanism

Abstract: Skeletal muscle atrophy is a pathological condition characterized by the loss of strength and muscle mass, an increase in myosin heavy chain (MHC) degradation and increase in the expression of two muscle-specific ubiquitin ligases: atrogin-1 and MuRF-1. Angiotensin II (AngII) induces muscle atrophy. Angiotensin-(1-7) [Ang-(1-7)], through its receptor Mas, produces the opposite effects than AngII. We assessed the effects of Ang-(1-7) on the skeletal muscle atrophy induced by AngII. Our results show that Ang-(1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
102
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 75 publications
(116 citation statements)
references
References 65 publications
7
102
0
1
Order By: Relevance
“…In this context, Ang-(1-7) has a demonstrated anti-atrophic effect on Ang-II-dependent and -independent models, such as in disuse, sepsis, or Ang-II-induced cachexia. 11,[15][16][17][18] This study is highly relevant for muscle biology, particularly with regard to pathological statuses that induce muscle atrophy, such as sepsis, that cannot be treated with oral drug therapies or exercise. Therefore, further studies should be conducted to assess the therapeutic …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this context, Ang-(1-7) has a demonstrated anti-atrophic effect on Ang-II-dependent and -independent models, such as in disuse, sepsis, or Ang-II-induced cachexia. 11,[15][16][17][18] This study is highly relevant for muscle biology, particularly with regard to pathological statuses that induce muscle atrophy, such as sepsis, that cannot be treated with oral drug therapies or exercise. Therefore, further studies should be conducted to assess the therapeutic …”
Section: Discussionmentioning
confidence: 99%
“…For IP treatment, 50 µL of phosphate-buffered saline (PBS), Ang-(1-7) (0.8 mM), PAMAM-OH (0.4 mM), and the complex Ang-(1-7)/PAMAM-OH (2:1) were IP injected three times a week starting 24 h before cast immobilization. For osmotic pump delivery, PBS, Ang-(1-7) (100 ng/kg/min), PAMAM-OH (1 ng/kg/min), and the Ang-(1-7)/PAMAM-OH complex (2:1 molar ratio) were osmotically infused through micropumps (Alzet-Durect, Cupertino, CA, USA), as previously described, [15][16][17][18] 24 h before cast immobilization. After experimentation, the animals were euthanized under anesthesia and the gastrocnemius (GAST) muscles were dissected, removed, and rapidly frozen and stored at -80°C until processing.…”
Section: Electrophoresis Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The alternative arm of RAS or non-classical RAS, is formed by ACE-2 that induces the synthesis of Ang-(1-7) peptide that acts via Mas receptor producing contrary effects than classical RAS [24,28]. In this context, our previous studies have shown that Ang-(1-7) prevents muscle atrophy induced by Ang-II, lipopolysaccharides, and disuse through the Mas receptor [29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Wheat germ agglutinin (WGA) staining labels glycoproteins at the sarcolemma [29,31]. To stain the samples, freshly-frozen TA muscles were cryosectioned (8 µm) and placed on glass slides.…”
Section: Wheat Germ Agglutinin Stainingmentioning
confidence: 99%